INCIDENCE OF PARAVALVULAR LEAKAGE IN PATIENTS UNDERGOING AORTIC VALVE REPLACEMENT (REMUNOM, 2024)
Introduction: Aortic stenosis is a common degenerative condition in the elderly. Definitive treatment is usually surgical, with surgical aortic valve replacement (SAVR) or catheter aortic valve implantation (TAVI). Paravalvular leak (PVL) is a complication that can occur after valve replacement surgery, requiring intervention. Objective: To evaluate the incidence of paravalvular valve leak in patients who underwent SAVR and TAVI. Material and Method: We evaluated 25 studies published between January 2018 and November 2023 presenting groups of individuals who underwent SAVR or TAVI and had PVL as a complication. The main databases used were the Scielo and PubMed platforms. Results: It was observed that, shortly after discharge, 27% of the patients in question had some degree of paravalvular leak after TAVR, while among the patients who underwent AVRS, the incidence of PVV was 7.2%. After 6 months or more of discharge, 20.9% of TAVR patients still had TAVR, compared with 5.7% of SAVR patients.Conclusion: In the immediate and late postoperative periods, the incidence of PVL is lower in patients undergoing SAVR than in those undergoing TAVI, in all grades - mild, moderate and severe.